Inhibitory Effect of KP-A038 on Osteoclastogenesis and Inflammatory Bone Loss Is Associated With Downregulation of Blimp1 - Ihn, Hye Jung; Lee, Taeho; Lee, Doohyun; Bae, Jong-Sup; Kim, Sang-Hyun; Jang, Il Ho; Bae, Yong Chul; Shin, Hong-In; Park, Eui Kyun (Frontiers in Pharmacology, 2019)
Excessive osteoclastic activity results in pathological bone-resorptive diseases, such as osteoporosis, periodontitis, and rheumatoid arthritis. As imidazole-containing compounds possess extensive therapeutic potential for the management of diverse diseases, we synthesized a series of imidazole derivatives and investigated their effects on osteoclast differentiation and function. In the present study, we found that a novel imidazole derivative, KP-A038, suppressed receptor activator of nuclear factor-κB ligand (RANKL)-mediated osteoclastogenesis and bone-resorbing activity in vitro and attenuated lipopolysaccharide (LPS)-induced bone destruction in vivo. KP-A038 significantly inhibited the induction of nuclear factor of activated T-cells cytoplasmic 1 and the expression of its target genes, including tartrate-resistant acid phosphatase(Acp5), cathepsin K (Ctsk), dendritic cell-specific transmembrane protein (Dcstamp), and matrix metallopeptidase 9 (Mmp9). KP-A038 upregulated the expression of negative regulators of osteoclast differentiation, such as interferon regulatory factor-8 (Irf8) and B-cell lymphoma 6 (Bcl6). Consistently, KP-A038 downregulated the expression of B lymphocyte-induced maturation protein-1 (Blimp1 encoded by Prdm1), a repressor for Irf8 and Bcl6. Moreover, administration of KP-A038 reduced LPS-induced bone erosion by suppressing osteoclast formation in vivo. Thus, our findings suggest that KP-A038 may serve as an effective therapeutic agent for the treatment and/or prevention of bone loss in pathological bone diseases, including osteoporosis and periodontitis.